Computational analysis of ionizing radiation-induced shape parameter changes on bacterial cell - H. G. Badalyan; Sh. I. Astanyan
The purpose of this work was computational analysis of ionizing radiation-induced shape parameter changes on bacterial cell. For our investigation we have radiated Escherichia coli and Pseudomonas aeruginosa. Strains of Escherichia coli were exposed to UV light for 10 and 15 minutes, Pseudomonas aeruginosa were exposed to gamma radiation for 15 and 30 minutes respectively. The results of radiation showed that gamma radiation causes decrease of area and perimeter and increase of shape parameter. Results for Escherichia coli were a little different after 10 minutes area and perimeter were decreased compared with control, shape parameter was increased but after 15 minutes area and perimeter were increased, shape parameter was decreased.
Keywords: Physics; Cross-Disciplinary